A structural modeling on food safety knowledge, attitude and behaviour among Bum Bum Island Community of Semporna, Sabah - Lim, Tee-Ping; Chye, Fook Yee; Mohd Rosni Sulaiman; Norazah Mohd Suki; Lee, Jau-Shya (Elsevier BV, 2016)
The objective of this study was to evaluate the relationship among food safety knowledge, attitude and behavior in Bum Bum Island community, Semporna, Sabah. Proportional stratified sampling method was used in this survey. A total of 250 respondents were selected randomly from ten villages in Bum Bum Island. Face-to-face interview was conducted to complete the questionnaire. In general, respondents exhibited average food safety knowledge level especially in their awareness of personal hygiene and kitchenware hygiene. Food safety attitude of the community was found strongly affected their food safety behavior in positive way, which was proven by the highest standard b among variables tested (b1 ¼ 0.885, p < 0.05). However, food safety knowledge was negatively affected the food safety behavior of the respondents (b1¼ 0.128, p < 0.05). Our result confirmed that Structural Equation Modeling (SEM) was successfully used to model the relationship among food safety knowledge, attitude and behavior.